Pain Interference Is Associated With Psychological Concerns Related to Falls in Community-Dwelling Older Adults: Multisite Observational Study. Issue 10 (1st October 2014) - Stubbs, Brendon; Eggermont, Laura H.P.; Patchay, Sandhi; Schofield, Pat A.
Abstract : Background: Pain interference and psychological concerns related to falls (PCRF) are pervasive phenomena among community-dwelling older adults, yet their association remains elusive. Objective: The purpose of this study was to establish whether pain interference is associated with PCRF in community-dwelling older adults. Design: This was a multisite cross-sectional study. Method: Two hundred ninety-five community-dwelling older adults (mean age=77.5 years, SD=8.1; 66.4% female) participated in the study. All participants completed the Brief Pain Inventory (BPI) interference subscale, Short Falls Efficacy Scale–International (FES-I), Activities-specific Balance Confidence Scale (ABC), modified version of the Survey of Activities and Fear of Falling in Elderly Scale (mSAFFE), and Consequences of Falling Scale (CoF). Hierarchical multiple regression analysis were conducted. In the first step of the study, sociodemographic and known risk factors for psychological concerns related to falls were inserted into the model, followed by the BPI interference subscale score in the second step. Results: One hundred sixty-nine participants (57.3%) reported some pain interference. The BPI interference subscale was highly correlated with all PCRF ( r >.5, P <.0001). After the adjustment for established risk factors, the BPI interference subscale significantly increased the variance in the Short FES-I ( R 2 change=13.2%), ABC ( R 2 change=4.7%), mSAFFE ( R 2 change=5.0%), and CoF ( R 2 change=10.0%). Pain interference was a significant and independent predictor in the final model for the Short FES-1 (β=0.455, P <.001), ABC (β=−0.265, P <.001), mSAFFE (β=0.276, P <.001), and CoF (β=0.390, P <.001). Limitations: The study was cross-sectional. Conclusions: Pain interference is an important contributing factor in each of the psychological concerns related to falls. Pain interference had the strongest impact on reducing falls efficacy and increasing older adults' concerns about the consequences of falling.